Lower East Side Memories A Jewish Place in America - Diner, Hasia R. (Princeton University Press, 2020)
Manhattan's Lower East Side stands for Jewish experience in America. With the possible exception of African-Americans and Harlem, no ethnic group has been so thoroughly understood and imagined through a particular chunk of space. Despite the fact that most American Jews have never set foot there--and many come from families that did not immigrate through New York much less reside on Hester or Delancey Street--the Lower East Side is firm in their collective memory. Whether they have been there or not, people reminisce about the Lower East Side as the place where life pulsated, bread tasted better, relationships were richer, tradition thrived, and passions flared. This was not always so. During the years now fondly recalled (1880-1930), the neighborhood was only occasionally called the Lower East Side. Though largely populated by Jews from Eastern Europe, it was not ethnically or even religiously homogenous.